2007
DOI: 10.1038/modpathol.3800930
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in human gastric mucosa infected with Helicobacter pylori

Abstract: Pathogenic mechanisms associated with Helicobacter pylori infection enhance susceptibility of the gastric epithelium to carcinogenic conversion. We have characterized the gene expression profiles of gastric biopsies from 69 French Caucasian patients, of which 43 (62%) were infected with H. pylori. The bacterium was detected in 27 of the 42 antral biopsies examined and in 16 of the 27 fundic biopsies. Infected biopsies were selected for the presence of chronic active gastritis, in absence of metaplasia and dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Microarray data were used to determine the global gene expression of infected cells. Microarray data showed up/down regulation of gene expression related to immune response, cell cycle, cell growth, and signal transduction, which may support the hypothesis that H pylori infection causes cancer development [4,11,13,20] . However, the data did not present a clear mechanism of carcinogenesis in a systematic manner.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Microarray data were used to determine the global gene expression of infected cells. Microarray data showed up/down regulation of gene expression related to immune response, cell cycle, cell growth, and signal transduction, which may support the hypothesis that H pylori infection causes cancer development [4,11,13,20] . However, the data did not present a clear mechanism of carcinogenesis in a systematic manner.…”
Section: Discussionsupporting
confidence: 49%
“…The expression of genes significantly changed (P < 0.05) by H pylori infection in the microarray [4,11,13,20] data was examined, and genes related to the immune response were identified and collected. A total of 39 filtered genes (Table 1) were obtained.…”
Section: Searching Genes Related To H Pylori Infection (Step 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that a premalignant molecular signature can be detected in the most severely infected cases before any histological evidence of malignancy. 25 We identified 32 significant GO term annotations mainly involved in the intracellular biosynthetic process, the cellular biosynthetic process, phosphorylation, the purine ribonucleotide biosynthetic process, the purine nucleotide biosynthetic process, the ribonucleotide biosynthetic process, the purine ribonucleotide metabolic process, the purine nucleotide metabolic process and the ribonucleotide metabolic process. It has been reported that a large number of GO term annotations have taken part in gastric cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…19 Results from Figure 1 also revealed that a total of 124 genes were differentially expressed between H. pylori-positive and -negative groups in six CAG samples with IL-1B-31CC/-511TT genotypes, and the samples of antral mucosa were divided correctly into two clusters by these genes. Hofman et al 25 have characterized the gene expression profiles of 42 antral biopsies corresponding to 27 patients infected with H. pylori. A total of 165 genes (92 upregulated and 73 downregulated) were defined as being differentially expressed between the gastric antrum of H. pylori-infected and non-infected patients.…”
Section: Discussionmentioning
confidence: 99%